HUBUNGAN EMOTIONAL EATING DENGAN KEJADIAN OBESITAS PADA MAHASISWA FAKULTAS ILMU KESEHATAN UPN "VETERAN" JAKARTA - Elshinta Rachmawati (2023)
Obesity is the third leading cause of chronic health problems. The obesity epidemic is one of the biggest global public health challenges that continues to increase rapidly. Based on Riskesdas data for 2018, 21.8% of adolescents aged 18 and over are obese. One of the factors that causes obesity is emotional eating behavior. Emotional eating can have an impact on general health due to excess energy intake and disruption of mental health. To identify the relationship between emotional eating with the incidence of obesity in students at the Faculty of Health Science UPN "Veteran" Jakarta. The research design used a cross-sectional study and stratified random sampling technique involving 108 respondents. Chi-square analysis results showed that there was a relationship between emotional eating, energy intake, protein intake, fat intake, and carbohydrate intake with the incidence of obesity in students of the Faculty of Health Sciences UPN "Veteran" Jakarta (p value < 0,05) with OR values (OR 95% CI = 3,32; 27,21; 4,479; 4,195;-) and there is no relationship between stress levels and the incidence of obesity in students of the Faculty of Health Sciences UPN "Veteran" Jakarta (p value = 0,409; OR 95% CI = 1,442). Data collection in research has limited time to dig deeper into the causes of emotional eating so that further studies are needed with a longer data collection time.